PENGARUH PENILAIAN KESEHATAN LPD DENGAN METODE CAMEL TERHADAP PERTUMBUHAN LABA DI LPD DESA ADAT AMBENGAN - MERTYANI SARI DEWI; KETUT SEPSI KASTIANI (GANEC SWARA, 2023)
In this study, a quantitative approach was used to study the effect of CAR, KAP, CPRR, management, ROA, BOPO, LACLR, and LDR on profit growth in LPD Ambengan Customary Village individually and together. The Monthly Report of LPD Ambengan Customary Village consists of the population, with a sample of monthly reports from 2018 to 2022. Data were collected through document recording, and analysis was performed using the SPSS program for multiple linear regression. While KAP, CPRR, management, BOPO, and LDR had a significant positive impact, CAR did not affect profit growth. In contrast, ROA and LACLR have a significant negative impact. In addition, CAR, KAP, CPRR, management, ROA, BOPO, LACLR, and LDR collectively influence profit growth.